Electronic modulation of cobalt–molybdenum oxide via Te doping embedded in a carbon matrix for superior overall water splitting. Issue 15 (20th June 2022) - Wang, Luqi; Yu, Hanzhi; Zhao, Sheng; Ma, Hui; Li, Linlin; Hu, Feng; Li, Lei; Pan, Hui; El-Khatib, K. M.; Peng, Shengjie
Abstract : Te-doped CoMoO3 supported on a carbon matrix exhibits superior electrocatalytic activity, which is attributed to the modulation of the local electronic structure and sufficient exposure of active sites by the doping of Te. Abstract : Heteroatom incorporation into the lattice of host materials as bifunctional electrocatalysts is developed as an effective strategy to promote electrochemical water splitting but challenges remain in the modulation of catalytic activity. Herein, Te-doped CoMoO3 supported on a carbon matrix (Te-CoMoO3 @C) is synthesized by lattice engineering with filter paper as a sacrificial carrier and carbon source. The doping of Te can effectively modulate the local electronic structures of Co and Mo sites and significantly boost the electrochemical active surface area and electron transfer, which optimize the reactivity of reaction intermediates with the electrocatalysts. Moreover, the filter paper-derived carbon as a carrier guarantees adequate exposure of the surface active sites and enhances catalytic stability. Impressively, the optimized Te-CoMoO3 @C only requires overpotentials of 76 and 215 mV at 10 mA cm −2 for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), respectively. As expected, Te-CoMoO3 @C exhibits a low cell voltage of 1.54 V at 10 mA cm −2 for water splitting. This work gives new insights into the rational design of metal oxides and opens up a novel strategy toward preparing efficient bifunctional electrocatalysts.